Dry matter accumulation and mineral nutrition of arracacha in response to nitrogen fertilization - Magolbo, Luis Augusto [UNESP]; Carmo, Ezequiel Lopes do; Garcia, Emerson Loli [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Leonel, Magali [UNESP] (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to evaluate the effect of nitrogen fertilization on the growth and yield of arracacha (Arracacia xanthorrhiza), as well as on the plant's nutrient uptake, distribution, and removal. The experiment was carried out in a typical Oxisol, with sandy texture. A randomized complete block design was used, with four replicates. The treatments consisted of five N rates: 0, 50, 100, 200, and 400 kg ha(-1). The plots were composed of three 8-m-length rows, spaced at 0.60 m between rows and 0.40 m between plants. The plants were harvested after an 8-month cycle. Nitrogen fertilization significantly increased the proportion of N and S accumulated in stems, and of Ca, Mg, Fe, and Mn in leaves. N supply increased Zn distribution to stems and leaves, whereas high N rates increased Cu allocation to stems more than to the rootstock. High N rates increase plant dry matter (DM) production and nutrient uptake and removal, but do not result in the greatest yield due to the greater development of leaves and stems, and to the lower allocation of DM in storage roots.
Keywords: Arracacia xanthorrhiza; dry matter allocation; nutrient accumulation; nutrient concentration; storage root